Aktualisasi Nilai – Nilai Aswaja Melalui Tradisi Manaqib di Masyarakat Majalengka - Ulfa Khusna Lailiyah; Najwa Ajlina Nur Azizah; Nurul Mubin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to examine how the tradition of manaqib contributes to the actualization of the values of Ahlussunnah wal Jamaah (Aswaja) within the society of Majalengka. As a cultural-religious heritage of Islam Nusantara, manaqib is not merely seen as a spiritual ritual, but also as a vital medium for instilling Islamic values that emphasize moderation (tawassuth), tolerance (tasamuh), balance (tawazun), and justice (i’tidal). Using a qualitative descriptive approach and literature review method, this study draws on various academic sources and journal articles. The findings reveal that manaqib plays a strategic role in shaping the spiritual character of society, strengthening traditional religious identity, and preserving social cohesion and harmony. However, the tradition faces significant challenges in the modern era, such as the rise of puritan movements and shifting societal lifestyles. Therefore, revitalization efforts through contextual approaches and the use of digital media are crucial to ensure the continued relevance and transmission of Aswaja values to future generations.